2016
DOI: 10.1097/icb.0000000000000213
|View full text |Cite
|
Sign up to set email alerts
|

Two Cases of Acute Endophthalmitis After Intravitreal Dexamethasone Implant Injection

Abstract: Intravitreal dexamethasone implant-associated endophthalmitis is an uncommon and a challenging situation. Intravitreal antibiotics may lead to favorable visual outcomes without the need for a pars plana vitrectomy and implant removal in selected cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(29 citation statements)
references
References 18 publications
1
28
0
Order By: Relevance
“…Pars plana vitrectomy with removal of the implant has been recommended as it has been hypothesized that the infectious agent may be stationed inside the device and the steroid itself may weaken the host’s defense mechanisms 3, 4. On the other hand, two cases have also been successfully managed by administration of intravitreal antibiotics, without vitrectomy or implant removal 5 . These cases had better presenting visual acuity and less severe clinical features at presentation and were culture-negative.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pars plana vitrectomy with removal of the implant has been recommended as it has been hypothesized that the infectious agent may be stationed inside the device and the steroid itself may weaken the host’s defense mechanisms 3, 4. On the other hand, two cases have also been successfully managed by administration of intravitreal antibiotics, without vitrectomy or implant removal 5 . These cases had better presenting visual acuity and less severe clinical features at presentation and were culture-negative.…”
Section: Discussionmentioning
confidence: 99%
“…Sustained release intravitreal dexamethasone (DEX) implant, available as Ozurdex (Allergan, Inc, Irvine, CA), is approved for the treatment of diabetic macular edema (DME) following a randomized, masked, sham-controlled phase III clinical trial that demonstrated its efficacy and safety 1 . Endophthalmitis following intravitreal injections is not uncommon owing to the increasing number of injections; 2 however, there are very few reports of endophthalmitis after an intravitreal DEX implant 1, 3, 4, 5. This case adds to the literature on complications following administration of an intravitreal DEX implant and discusses the challenges faced while managing this scenario.…”
Section: Introductionmentioning
confidence: 99%
“…This is consistent with the outcome in two cases of endophthalmitis following DEX implants. [15] Admittedly, our patient had better visual acuity at initial presentation compared with that of the patient treated by Marchino et al ,[5] whose BCVA was only light perception. This reflects that the severity of the infection, and consequently its prognosis, are directly influenced by the level of initial visual acuity and the general condition of patients’ eyes.…”
Section: Discussionmentioning
confidence: 48%
“…This is similar to previously reported cases of acute endophthalmitis following DEX implants. [567815] Endophthalmitis following an intravitreal insertion of DEX implant has no established treatment guideline, in contrast to acute endophthalmitis after cataract extraction that has a detailed treatment algorithm constructed by the Endophthalmitis Vitrectomy Study. [17] In the current report, the authors did not opt for surgical intervention, and rather chose to closely monitor the patient's condition after treatment with intravitreal antibiotics.…”
Section: Discussionmentioning
confidence: 99%
“… 50 The dexamethasone delivery system may migrate into the anterior chamber in pseudophakic or aphakic eyes, 51 which requires surgical removal ( Figure 2 ). 52 Less frequently reported complications include endophthalmitis, 53 acute retinal necrosis due to varicella zoster virus, 54 and retinal and vitreous hemorrhage due to retinal impact during injection. 55 …”
Section: Dexamethasonementioning
confidence: 99%